Treatment of post-COVID-19 patients with chronic recurrent prostatitis: efficacy of recombinant interferon α-2b medications - Kh. S. Ibishev; Yu. L. Naboka; P. A. Krainiy; I. A. Gudima; A. D. Plyakin; J. O. Prokop; A. V. Ilyash (Вестник урологии, 2023)
Introduction. The tactics of managing and treating patients with chronic recurrent bacterial prostatitis (CRBP) in some cases is a difficult-to-treat condition for a practicing urologist. This circumstance occurs because the disease has several predisposing factors, a complex and multifaceted pathogenesis, and certain difficulties in diagnosis and treatment.Objective. To study the effectiveness of recombinant interferon α-2b medications in post-COVID-19 patients with chronic recurrent prostatitis against the background of antibiotic multi-drug resistance of microorganisms verified in prostate secretion.Materials and methods. The treatment of 52 post-COVID-19 patients with CRBP was analyzed, divided into three therapy-dependent groups. Group 1 patients (n = 18) received antibiotic therapy (ABT): Levofloxacin 500 mg q.d. PO for 28 days. Group 2 patients (n = 18) underwent combined therapy: ABT supplemented with recombinant interferon α-2b with an antioxidant complex of vitamins E and C (“Viferon®” rectal suppositories) 3.000.000 IU b.i.d. PR q12h for 28 days. Group 3 patients (n = 16) received monotherapy with recombinant interferon α-2b with an antioxidant complex of vitamins E and C (“Viferon®”rectal suppositories) 3.000.000 IU b.i.d. PR q12h for 28 days. The follow-up period was 6 months with monitoring of clinical and laboratory parameters assessed before treatment, after 1, 3 and 6 months from the start of therapy.Results. Based on the monitoring of the clinical picture and laboratory parameters, after 1 follow-up month, there was a significant decrease in the symptoms of the disease in all study groups. However, after 3 and 6 follow-up months, this trend was observed only in patients of groups 2 and 3 receiving recombinant interferon alfa-2b with an antioxidant complex (vitamins E and C).Conclusions. Strengthening the standard CRBP-therapy with recombinant interferon α-2b with an antioxidant complex of vitamins E and C makes it possible to normalize both clinical and laboratory parameters in most patients.